Gain and radiation improvement technique for rectangular patch antenna - Satthamsakul, S.; Puntheeranurak, S.; Benjankaprasert, C.; Anantrasirichai, N.; Wakabayashi, T. (My University, 2009)
This paper proposed the techniques for improved gain and radiation patterns include bandwidth enhancement of patch antenna by cutting slots in the ground plane. We proposed three styles of slot cut in the ground plane. There are narrow slot, wide slot, and wide slot with conductor strips. Each style is shown the gain improvement with wideband use in X-band communication systems. Finally, the gain is 6.96 dBi at frequency 10.5 GHz and the average gain from 8 to 10.5 GHz is 4.97 dBi. The radiation pattern shown the low back lobe with good directivity.
Keywords: Gain improvement; Patch antenna; Slot in the ground plane; Wideband